First Synthesis of a G-2 Melamine Dendrimer with Serinolic Peripheral Groups - Darabantu, Mircea; Pintea, Monica; Fazekas, Marijana; Lameiras, Pedro; Berghian, Camelia; Delhom, Isabelle; Silaghi-Dumitrescu, Ioan; Ple, Nelly; Turck, Alain (Letters in Organic Chemistry, 2006)
The first convergent and non-protective synthesis of a G-2 melamine dendrimer having (1S,2S)-1,3- dihydroxy-1-(4-nitrophenyl)-prop-2-ylamino units as peripheral groups (from l-p-nitrophenylserinol) and piperazine as linker is described to occur in five linear steps and 27% overall yield. The restricted rotation about Csp2(s-triazine)-N(exocyclic) bonds, exhibited by all compounds, is discussed as relevant.
Keywords: melamine